Ipsilateral fractures of both the proximal and distal humerus; the ‘floating arm injury’ in children - Gogoi, Paragjyoti; Das, Aditi; Dhar, Arijit; Roy, Rajdeep (International Journal of Research in Orthopaedics, 2021)
Proximal humerus fractures are usually associated with other injuries in and around the shoulder joint like clavicle fracture, acromion process fracture, coracoid process fracture, and dislocation of the shoulder joint or acromion-clavicular joint. Similarly, distal humerus fractures are normally associated with fractures of olecranon, radial head or dislocation of the elbow joint itself. However, simultaneous fracture of both the ends of humerus is rarely encountered. Literature search does reveal only a few cases of such type. This variety is also termed as floating arm. We are presenting here two cases of fracture of both the proximal and distal end of same humerus following fall from height, one of which the proximal humeral fracture was Gustillo-Anderson type II open fracture. The patient was managed by wound debridement and open reduction and fixation of the proximal fracture followed by closed manipulation and K wire fixation of the distal fracture. The second case was also managed by closed reduction and K wire fixation of both the fractures.